Hierarchical Inference in Sound Change: Words, Sounds, and Frequency of Use - Kapatsinski, Vsevolod (Frontiers in Psychology, 2021)
This paper aims examines the role of hierarchical inference in sound change. Through hierarchical inference, a language learner can distribute credit for a pronunciation between the intended phone and the larger units in which it is embedded, such as triphones, morphemes, words and larger syntactic constructions and collocations. In this way, hierarchical inference resolves the longstanding debate about the unit of sound change: it is not necessary for change to affect only sounds, or only words. Instead, both can be assigned their proper amount of credit for a particular pronunciation of a phone. Hierarchical inference is shown to generate novel predictions for the emergence of stable variation. Under standard assumptions about linguistic generalization, it also generates a counterintuitive prediction of a U-shaped frequency effect in an advanced articulatorily-motivated sound change. Once the change has progressed far enough for the phone to become associated with the reduced pronunciation, novel words will be more reduced than existing words that, for any reason, have become associated with the unreduced variant. Avoiding this prediction requires learners to not consider novel words to be representative of the experienced lexicon. Instead, learners should generalize to novel words from other words that are likely to exhibit similar behavior: rare words, and the words that occur in similar contexts. Directions for future work are outlined.